The Effect of Return on Asset (ROA) and Return on Equity (ROE) on Company Value in Cigarette Companies Listed on the Indonesia Stock Exchange in 2021 – 2023 - Nurpratiwi, Anggi Usmayantin; Ernawati , Ayu; Latifah, Maulani; Nurmala , Mila; Nisriina , Nisriina; Anggraeni, Silvi Surya (LPPM Universitas Sebelas April, 2025)
The purpose of this study is to determine how ROA and ROE affect the value of the company. The subject of this quantitative research is a cigarette company listed on the Indonesia Stock Exchange from 2021 to 2023. Four observational data were collected after the purposive sampling method was used to select the study sample. Data from the Annual Report was used in this study. This data was tested by multiple linear regression. The results of the study showed that ROA and ROE partially did not affect the company's value.